Covid-19 outbreak in Malaysia: data sharing benefits during pandemic - Osman, Malina; Awang Hamat, Rukman (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Real epidemiology data related to cases during Covid-19 pandemic is very crucial. In epidemiology, both descriptive and analytic reports on confirmed cases are essential for the purpose of modelling, infection disease management, prevention, surveillance as well as knowledge dissemination. Precise measurement of the factors that influences the course of an epidemic is necessary (1), therefore elements included in forecasted data should be based on real situations in the fields.